1993
DOI: 10.1002/dev.420260502
|View full text |Cite
|
Sign up to set email alerts
|

Importance of prenatal nutrition to the development of a precocial chick

Abstract: The developmental maturity of hatchling birds varies greatly across the altricial-precocial continuum and these differences are related to the relative proportions of yolk and albumen in a species' egg. In general, the more precocial the chick the greater the proportion of yolk in its egg. Egg composition can also vary within species with unknown consequences for the developing embryo. The present research sought to determine the importance of egg composition to avian development by experimentally removing 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 44 publications
(38 reference statements)
6
44
2
Order By: Relevance
“…The eggs of chickens contain yolk, which consists of water, fat, and proteins and primarily determines the degree of development of the chick at hatching. The other component of the egg, albumen, mainly (approximately 95%) contains water and amino acids, which are used by the developing embryo for wholebody protein synthesis and growth (23,32,33). As previously shown (23,34), extraction of albumen from the egg was found to reduce total embryonic weight toward the end of incubation.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…The eggs of chickens contain yolk, which consists of water, fat, and proteins and primarily determines the degree of development of the chick at hatching. The other component of the egg, albumen, mainly (approximately 95%) contains water and amino acids, which are used by the developing embryo for wholebody protein synthesis and growth (23,32,33). As previously shown (23,34), extraction of albumen from the egg was found to reduce total embryonic weight toward the end of incubation.…”
mentioning
confidence: 78%
“…The other component of the egg, albumen, mainly (approximately 95%) contains water and amino acids, which are used by the developing embryo for wholebody protein synthesis and growth (23,32,33). As previously shown (23,34), extraction of albumen from the egg was found to reduce total embryonic weight toward the end of incubation. Similar to exposure to chronic hypoxia, relative brain weight was spared, indicating that growth was reduced in a disproportionate way in both models.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Studies examining the effects of water loss from eggs during incubation have shown that differences in wet embryo mass tend to be correlated with water content of the embryo and that eggs losing the most water tend to produce embryos with the lowest mass (Davis et al, 1988;Tullett and Burton, 1982). Removing albumen from chicken Gallus gallus eggs caused a reduction in hatchling size (Hill, 1993;Finkler et al, 1998) and resulted in hatchlings with a reduced yolkfree wet body mass (Finkler et al, 1998). Though hatchlings emerging from eggs from which albumen had been removed were smaller (i.e.…”
Section: Water Relations and Hatchling Massmentioning
confidence: 99%